Characteristics of postmidnight L band scintillation in the transition region from the equatorial to midlatitudes over the Indian longitude sector using COSMIC, C/NOFS, and GPS measurements. Issue 12 (16th December 2015) - Paul, A.; Haralambous, H.; Oikonomou, C.
Abstract: Occurrence of L band scintillations around midnight and postmidnight hours have not been well studied and reported from the higher equatorial latitudes in the transition region from the equatorial to midlatitudes over the Indian longitude sector. The present paper reports cases of postmidnight L band scintillation observations by COSMIC during March 2014 over the Indian longitude sector. GPS S 4 measurements from the International Global Navigation Satellite Systems Service station at Lucknow (26.91°N, 80.96°E geographic; magnetic dip: 39.75°N) corroborate occurrence of postmidnight scintillations. The F region vertical upward velocities around the magnetic equator during evening hours have been used to understand the possibility of impact of irregularities generated over the magnetic equator at latitudes north of 30°N. Postmidnight L band scintillations at latitudes greater than 30°N without corresponding premidnight scintillations present interesting scientific scenario and give rise to suggestions of (1) any coupling mechanism between the equatorial and midlatitudes through which irregularities seeded in the midlatitudes may affect transionospheric satellite links at low latitudes or (2) irregularity generation at midlatitudes not connected with equatorial instabilities. Long‐term analysis of S 4 at L band measured by COSMIC over the Indian longitudes during March 2007–2014 exhibits a well‐defined longitude swath around 75–83°E of reduced (0.2 < S 4 < 0.4) or no scintillations which may be attributed to the longitudinal variability of scintillation occurrence following the global four‐cell pattern of ionospheric activity. Key Points: Postmidnight L band scintillations COSMIC and GPS observations in the transition region from equatorial to midlatitudes Longitudinal swath of reduced or no L band scintillations over India